Academic and special libraries in Croatia and their crisis preparedness: a survey (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. This research aimed to assess the state of crisis preparedness, management, and the potentials of crisis response in academic and special libraries in Croatia. The majority of academic and special libraries in Croatia are not a standalone institution: they are an integral part of other institutions or organisations, making their freedom in establishing crisis management actions limited. These libraries are specific in their or ganization, users and collections, and a significant part of them holds valuable heritage collections of old and rare library materials.Methodology. Data was collected through an online questionnaire that was sent to all Croatian academic and special libraries. The questionnaire included questions about risk assessment, the state of crisis management, current experience, and education of the staff, as well as the levels of crisis preparedness and that of crisis occurrences. Since a significant percentage of Croatian academic and special libraries is located in Zagreb, emphasis was laid on recent disasters (earthquakes and floods in 2020) and the way the libraries responded to them.Results. The results have shown considerable discrepancies in the equipment, conditions, and the crisis mitigation capacities among the surveyed libraries. They have shed light on the frequency of crisis situations and the ways libraries cope with them.Originality. The research contributes to the development of preservation of library materials by bringing new insights into crisis management in academic and special libraries in Croatia. The collected data will serve as a good basis for planning and organising collective education and targeted actions in improving heritage preservation at risk.
Keywords: academic libraries; cooperation; crisis preparedness; crisis response; heritage collections; special libraries